Cultivation of Spirulina platensis in human urine medium or/and fish liver oil medium (home design) - Abdulrraziq, Ahmed (Algerian Journal of Biosciences, 2023)
Spirulina platensis is one of the most significant algae that has attracted a lot of business interest as a novel natural product, which necessitates the development of a low-cost cultivation system to produce high yields. This study aims to evaluate the 30-day culture of S.platensis in a human urine mixture with or without fish liver oil medium (home design). The cultivation included eight conditions: Zarrouk's medium (control), human urine medium at 1:1 and 1:2 (v:v) concentrations, fish liver oil medium at 5/100 and 10ml/100ml concentrations, and finally mixture medium. The results show that S.platensis grew in all tested media with stable productivity. Nevertheless, Zarrouk's medium was significantly (P<0.05) higher than all tested media in all growth indicators. On the other hand, it was observed that Spirulina cultivation in the mixture medium was very satisfactory, yielding biomass (4.4g/L), a specific growth rate of 0.14 mg/L/day, a generation time of 2.7 days and total carbohydrate 53.0% (w/w), which was comparable to Zarrouk's medium, with biomass (5.2 g/L), a specific growth rate of 0.18 mg/L/day, a generation time of 3.2 days and total carbohydrate 38.0% (w/w). This study is a step in the right direction toward developing an affordable medium for Spirulina platensis cultivation